Exploring Design Concepts to Facilitate Van Life - Flodman, Lovisa (My University, 2026)
his thesis presents a family of design concepts developed through an exploration of user values within the camper van segment. The aim was to identify and address challenges associated with living in a camper van and to translate these insights into relevant design solutions. The thesis was carried out in collaboration with Lagun and Boat System Group and the project sought to provide valuable insights into a new market segment that the brand aims to enter and expand towards. The project was divided into two main phases. The first phase consisted of user studies, with the purpose of providing Lagun with valuable knowledge about their new target group. The second phase focused on concept development, translating insights from the user studies into design concepts. A combination of methods commonly used in user research and design projects was applied throughout the project, including methods for data collection, data analysis, ideation, and evaluation. The user studies resulted in two categories of takeaways. The first category consisted of insights that served as a foundation for the subsequent concept development phase. The second category consisted of broader insights intended to help the company better understand its new user group, including their perspectives, needs, and expectations in order to support Lagun in developing future products that align with users needs. The takeaways indicated that user challenges were spread across multiple areas of the van, rather than linked to one specific space. This directed the concept development phase to focus on adaptable, modular, and multifunctional solutions requiring minimal interior modification. The project resulted in a family of five related concepts, all compatible with Lagun’s planned rail system, which forms part of the company’s first step into this market expansion. Each concept was designed to fulfill a specific function or address challenging, inconvenient, or time-consuming situations that may arise in the context of camper van living
Keywords: Camper Van; Camper; Van life; Market Expansion; User Studies; User Value; Modularity; Concept Development; Concept Design; Concept Family